Photosensibility generation of singlet oxygen - García Fresnadillo, David (2010)
The present communication deals with the production of singlet oxygen photosensibility along the same it is intended to convey the following basic ideas: ¿What is the singlet oxygen? ¿How can you generate this chemical species?, paying special attention to the method of photosensitisation. Once produced the singlet oxygen, ¿how can you evaluate and quantify its production? and finally, ¿what is the reactivity of the singlet oxygen?, therefore, ¿what are the potential areas of application of this chemical species?.